Improving legislative activities of the Armed Forces of Ukraine - Коропатнік, Ігор Михайлович; Кузьмич, Ігор Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This article examines the current state and the ways of improving legislative activities of the militarycommand of the Armed Forces of Ukraine. In addition, authors discuss the disadvantages of the current legalframework, which adversely affects the quality of the professional activities of the Armed Forces of Ukraine.